Early farming in Dalmatia : Pokrovnik and Danilo Bitinj: two neolithic villages in south-east Europe - Moore, A. M. T. (Archaeopress Publishing Ltd, 2019)
This text investigates the expansion of farming from its centre of origin in western Asia through the Mediterranean into southern Europe. Focusing on Dalmatia, it addresses several key questions, including when and how farming reached the area, what was the nature of this new economy, and what was its impact on the local environment.